The Role of Monologue Technique in prolepsis Events in Bave Nazes Novel ‘Hewara Nebihisti as a model. - Hassan, Shivan (Humanities Journal of University of Zakho, 2021)
A Novel as an important and wider literary genre from epical literature type, if it can‌t be said overall, but it comprises most the techniques and elements of narration. Accordingly, these techniques and elements are, as series, related to each other and they are usually complementary to each other. For instance, the dialogue wouldn‌t be produced without characters, also, without having a dialogue and characters, no conflict and events will be created and etc. Monologue also, with its types as major technique that has its sensitive impact on in the literary works in general and in the novels particularly, it has a great role. So, if a novelist is a skillful one, he/she will get the best advantages from that sensitive technique and makes the novel most effective in terms of technique. Bave Naze as a Kurdish experienced novelist, got a great benefit from Monologue technique in his novels and he abled to activate that technique to motivate ad progress the other techniques in his writing as well, the event in particular, which the Monologue Technique could directly change the events, that is, the study case of this research is a novel by Bave Naze entitled ”Hewara Nebihisti” which it is dealt with by the process of Monologue technique so effectively, in addition, the technique with its types enhanced the events of in the different settings of the novel, therefore, the title “ The Role of Monologue Technique in progressing Events in Bave Naze‌s Novel Hewara Nebihisti As model, is selected for this study.